A comparison between teachers' and pupils's tendency to use a representatives heuristics - Lamprianou, Thekla Afantiti; Williams, Julian; Lamprianou, Iasonas (2005)
This study builds on a previous research on children's probability conceptions and misconceptions due to the representatives heuristic. Rasch measurement methodology was used to analyse fresh data collected when a 10-item instrument was administered to a new sample for the teachers' sample, but a hierarchy of two levels is constructed for the pupils' responses. Each level is characterized by the ability t overcome typical representatives effects, namely recency, random-similarity, base-rate fequency and sample size. Less experienced teachers had a better performance on the instruments.The educational implications of our findings are discussed.